Individualizing risk: moral judgement, professional knowledge and affect in parole evaluations - Werther, Robert (The British journal of criminology, 2017)
Drawing from an ethnographic project within the California (USA) parole system, this article traces how field personnel evaluate individuals and attempt to anticipate future conduct. It troubles claims that risk has replaced dangerousness and deindividualized penal subjects. In this setting, rather than displaying a technocratic character, the evaluation of risk is highly individualizing and impressionistic. Individuals contingently assemble knowledges, devalue actuarial tools and privilege their experiential expertise, affect and the moral judgement of personhood. Even among those classified as ‘serious’ offenders, evaluation operates as a space for judging the potential danger of specific individuals. This is reflective, in part, of field personnel’s efforts to protect their professional standing in the face of the parole agency’s promotion of risk technologies.